NETWORK OF STAFF AND TEACHERS IN CHILDCARE SERVICES - Lipphardt, Anne-Marie; Hahner-Korinski, Renate; Blatnik, Stanko; Selimović, Sanja; Szalma, Eva; Arenas Romero, M. Begona; Pokorny, Svenja (Journal of Educational and Instructional Studies in the World, 2015)
In this paper we present the results of the project“Network of Staff and Teachers in Childcare Services”, which is being realized within the framework of the EU Lifelong Learning Programme. The state of the art in staff development in Early Childhood Education and Care is related to the fragmented situation of systems and provisions across the EU: a common vision for childcare services is currently lacking in Europe, just as levels of investment differ greatly between Member States. Also, the picture in relation to childcare workforce varies significantly. Given the varied backgrounds of the EU Member States, there are no common recommendations/curricula, and practitioners as well as institutions at the national/regional level have little possibilities of sharing them. For this reason, the project has established a network in ECEC staff development: it contributes to overcome local visions, by creating links between institutions/practitioners/professionals, and by collecting learning resources in ECEC and making them available to a larger audienc
Keywords: Early childhood education and care; learning resources; network; childcare workforce